INDIVIDUAL VARIATION IN THE STRUCTURE OF BILINGUAL GRAMMARS. - COHEN, CLARA; NABI, SYED WAQAR; HIGHAM, CATHERINE F.; PUTNAM, MICHAEL; KOOTSTRA, GERRIT JAN; VAN HELL, JANET G. (Language, 2021)
A bilingual's two languages can interact in their mind, but the mechanism of this interaction is still open to debate. In this article we employ a variant of gradient symbolic computation (GSC; Smolensky et al. 2014) to model the code-switched utterances of unbalanced Dutch-English bilinguals. We aimed to evaluate GSC as an appropriate architecture to model bilingual code-switching grammars, and to explore the extent of variability within and across individual bilingual speakers. The results indicate that the structure of individual grammars can vary widely from the structure of the grammar that emerges when the population is studied as a whole. We interpret these results as evidence that individual variation characterizes not only language processing (e.g. Fricke et al. 2019, Kidd et al. 2018), but also the structure of bilingual grammar itself.